Phenotypic plasticity to drought in seedlings of the warm season grass Panicum coloratum is related to collection site - Giordano, Mabel Cristina; Grimoldi, Agustin Alberto; Tomas, Maria Andrea (Wiley, 2019)
Phenotypic plasticity is the ability of organisms to modify their phenotype in response to environmental changes. We estimated and compared the amount of phenotypic plasticity in response to drought in seedlings of different accessions of two varieties (var. makarikariense and var. coloratum) of Panicum coloratum, an allogamous warm season perennial grass, introduced and collected in sites in Argentina with different precipitation regimes. Amount of phenotypic plasticity was quantified in shoot/root biomass, blade/sheath biomass, specific leaf area and leaf area ratio (leaf area/total biomass) and mean phenotypic plasticity was estimated. The two genetically distinct varieties differed in the phenotypic plasticity of leaf area ratio (p = 0.008, F‐test), with var. makarikariense showing higher phenotypic plasticity. Accessions within varieties differed in phenotypic plasticity of leaf area ratio, specific leaf area, blade/sheath biomass and mean phenotypic plasticity (p < 0.05, F‐test). A strong relationship (r = 0.82, p < 0.01, F‐test) between mean phenotypic plasticity of each accession and precipitation variability was found. Relationships between phenotypic plasticity of blade/sheath biomass and leaf area ratio with annual mean precipitation were r = 0.86 and r = 0.75, respectively (p < 0.05; p < 0.01, F‐test, respectively). Evidence of a decoupling between phenotypic plasticity of above‐ versus belowground characters was apparent; outcomes on the interpretation of the variability in phenotypic plasticity and the potential applications of this variability are presented.